Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Pada Madu Kembang Joyo Sriwijaya Di Palembang - Stefanni, Stefanni; Meirisa, Faradila (Universitas Multi Data Palembang, 2024)
The purpose of this study is to examine partially and simultaneously how the influence of marketing mix on purchasing decisions at Madu Kembang Joyo Sriwijaya in Palembang. The sample used amounted to 250 respondents. Data collection method with questionnaire and using Likert measurement scale. This research approach uses associative research. The technique for sampling uses non-probability sampling with the purposive sampling method. The results of this study show that the independent variable has a partial effect on the dependent variable. Simultaneously, the independent variable affects the dependent variable with a Sig < 0.05.